Depresi Ibu Rumah Tangga Dengan Hiv/Aids Sebelum Dan Sesudah Diberikan Spiritual Emotional Freedom Technique (Seft) - Desak Ketut Sugiartini; Dewi Aprelia Meriyani (STIKes Surya Global Yogyakarta, 2022)
ABSTRACT Background of Study : Housewives infected with HIV / AIDS are very vulnerable to experiencing depression. Apart from low self-esteem, housewives also feel that they have never done risky behavior but can be infected with HIV / AIDS. So it is necessary to provide spiritual emotional freedom technique (SEFT). The purpose of this study was to see differences in levels of depression before and after being given SEFT and differences in levels of depression in mothers before and after being given SEFT and conventional counseling.Methods : This research design used a quasi experiment with a pre post test approach. Where the respondents are at least 30 respondents divided into 2 groups, namely the SEFT group and the conventional counseling group. The sampling technique was simple random sampling, then the inclusion and exclusion criteria were assessed. Treatment and control were given for 1 month with meetings 3 times a week. The results were analyzed using paired and independent t-test.Results : The results found were that there were differences before and after in the SEFT group. Meanwhile, there was no significant difference in the conventional counseling group. Then the average level of depression in the treatment group was lower by -8.27 compared to the pain intensity in the group without being given SEFT (conventional counseling) with p value 0.05 and 95% CI (-12.5- (-4.07).Conclusion : The conclusion is that there is an effect of SEFT on reducing the level of depression of housewives with HIV / AIDS Keywords : Housewife, HIV/AIDS, Depression, SEFT